Inflammatory Response in Stroke: A Comparative Leukocyte Analysis in Hemorrhagic and Ischemic Stroke Patients at a Single Center in Jambi, Indonesia - Ardi Mardani; Ika Erna Uly Sirait; Tiara Monica; Valentin Widry Enggal (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Stroke remains a leading cause of mortality and morbidity worldwide. Inflammation plays a crucial role in the pathophysiology of both hemorrhagic and ischemic stroke. This study aimed to compare total leukocyte counts (TLC) in hemorrhagic and ischemic stroke patients to assess the inflammatory response and its potential implications for clinical outcomes. Methods: This retrospective study analyzed 74 stroke patients admitted to Abdul Manap Regional Hospital, Jambi, Indonesia, between January 2023 and December 2023. Patients were categorized into hemorrhagic (intracerebral hemorrhage) and ischemic stroke groups based on neuroimaging findings (CT scan or MRI). Demographic data, stroke severity (NIHSS score), and TLC obtained within 24 hours of admission were recorded. Independent t-tests and Mann-Whitney U tests were used for statistical analysis. Results: The study included 38 ischemic and 36 hemorrhagic stroke patients. The mean TLC was significantly higher in the hemorrhagic stroke group (11.4 ± 3.5 x10^9/L) compared to the ischemic stroke group (9.5 ± 2.8 x10^9/L) (p = 0.021). No significant correlation was found between TLC and stroke severity (NIHSS score) in either group. Conclusion: Hemorrhagic stroke patients exhibited a more pronounced early inflammatory response as evidenced by elevated TLC compared to ischemic stroke patients. Further research is needed to explore the prognostic value of TLC and the potential role of anti-inflammatory therapies in stroke management.